There is no planet B - Panayides, Angelos (My University, 2026)
08–13 November 2021, 3rd Emirates International Poster Festival (EIPF), Expo 2020 Culture and Science Association (NADWA), Dubai, United Arab Emirates There is no Planet B Invited participant In this 3rd edition, EIPF selected more than 100 designers to introduce poster images that reflect the theme of Expo 2020 Dubai “Connecting Minds, Creating the Future” in celebration of human brilliance and achievement. Organised by The Culture and Science Association (NADWA).